Efeito do hormônio gonadotrófico na maturação gonadal e na descarga do órgão elétrico no gênero Microsternarchus (Gymnotiformes:Hypopomidae) - Vargas, Jannise Ingrid Chong (Instituto Nacional de Pesquisas da Amazônia - INPA, 2014)
The fish belonging to the Order Gymnotiformes are distributed throughout the Central and South America, presenting its higher diversity in the Amazon. The group can be diagnosed by the presence of specialized organs that generate and detect electricity namely, respectively, electric organs (EO) and electroreceptors, which, working in tandem, compose the Electrogenic and Electrosensory System (EES). Gymnotiforms can be classified by the type of electric organ discharge (EOD) into two groups: pulsers and wavers. Microsternarchus is a gymnotiform genus described as monotypic, with a pulse-type EOD and congregating at least four lineages and eight sub-lineages, with high degree of genetic divergence. In this work experiments of gonadal induction were performed with the commercial product Ovaprim®, under two treatments: the first was a unique intramuscular dose of 0,5 μl/g while the second included a first dose of 0,5 μl/g and a second dose of same concentration 72 hours later. These inductions had as a main objective to analyze the effects of the hormone in the sexual maturation of captive fish and the respective variations in the EOD features, comparing the results between sexes, under the two treatments. All the individuals utilized belonged into a single lineage (C), and within it, three sub-lineages (C1, C2 and C5) were identified, by means of the DNA barcode. The sub-lineages C1 and C2 had already been described while C5 was discovered in this study. Each sub-lineage seems to be associated to specific affluent of Negro River. In the EOD recordings before and after each treatment it was possible to verify the effects of the hormone in some of the variable measured, but not in all, according to the sex. It became evident that Microsternarchus lineage C possesses an EOD with three phases and is widely distributed in the lower portion of the Basin. It was concluded, according to evidence from the gonado-somatic indexes (GSI) and EOD parameters, that both treatments provoked the start of gonadal maturation, in both males and females of Microsternarchus, but the total time of each treatment was not sufficient to allow the full maturation of the gonads neither a definitive sexual dimorphism in the EOD. The hormone’s effects (stage of gonadal maturation reached) was slightly different for males and females, according to the treatment.
Keywords: Indução hormonal; Maturação gonadal; Descarga do órgão elétrico